Mindsets religiöser Pluralität als Faktor in der (islamischen) Religionslehrer*innenbildung - Mauritz, Gerrit ca. 20./21. Jh. (Theo-Web, 2020)
The article explores and systematizes assumptions and beliefs about the religious plurality of lecturers at universities that are active in Islamic teacher training. The aim is to present the status quo for dealing with religious plurality in interreligious dialogue in university didactics. For this purpose, interviews were conducted with the lecturers in order to evaluate them in the context of a qualitative content analysis. The analysis resulted in three generalizable mindsets on religious plurality, which were encountered in the interviewees on a supraindividual basis. It also recorded the challenges that arise in interreligious dialogue at the university level and the implications associated with it.